2018
DOI: 10.2174/1573409914666180726092800
|View full text |Cite
|
Sign up to set email alerts
|

2D & 3D-QSAR Study on Novel Piperidine and Piperazine Derivatives as Acetylcholinesterase Enzyme Inhibitors

Abstract: In addition, obtaining models were validated by cross validation with cut off values of q2 > 0.5 and r2pred > 0.6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The non-cross-validation coefficient r 2 was 1.000 (>0.9), SEE was 0.008, and F was 507.314, indicating the greater fitting ability and robustness of the model [ 40 , 41 ]. The external test coefficient r 2 pred was 0.66 (>0.6), and SEP of the test set was 0.16, which specified the model also had well predictive ability [ 42 , 43 ] and the constructed CoMSIA model met the requirements [ 44 ]. The model was used to predict the comprehensive evaluation value Z of PAE derivatives’ flammability, biotoxicity, and enrichment multi-effect.…”
Section: Resultsmentioning
confidence: 99%
“…The non-cross-validation coefficient r 2 was 1.000 (>0.9), SEE was 0.008, and F was 507.314, indicating the greater fitting ability and robustness of the model [ 40 , 41 ]. The external test coefficient r 2 pred was 0.66 (>0.6), and SEP of the test set was 0.16, which specified the model also had well predictive ability [ 42 , 43 ] and the constructed CoMSIA model met the requirements [ 44 ]. The model was used to predict the comprehensive evaluation value Z of PAE derivatives’ flammability, biotoxicity, and enrichment multi-effect.…”
Section: Resultsmentioning
confidence: 99%
“…58 The Q ext 2 was 0.264, and the cSDEP value was 0.135, indicating that the model had high stability. 59 The parameters (Table 1) of the CoMSIA model of the bio-metabolic effect and concentration effect of FQs showed that the single effect of the CoMSIA model of FQs also met the evaluation requirements.…”
Section: Resultsmentioning
confidence: 92%
“…The primary aim of QSAR methods is using calculated numerical descriptors to build models that can correlate between molecular structure and biological activity. The major objective of QSAR is developing models to predict properties or activities of non‐synthesized compounds …”
Section: Introductionmentioning
confidence: 99%